Proses Berpikir Siswa SMP dalam Pemecahan Masalah Matematika Soal Cerita Ditinjau dari Gaya Kognitif Reflektif dan Impulsif - Fahmi Ramadhan; Hajidin Hajidin; Zainal Abidin (Universitas Syiah Kuala, 2019)
The thought process is very important in learning mathematics, especially in problem solving. By knowing the thought process didwa then the teacher can design an efficient learning model. The purpose of this study was to determine the thinking of students MTsN Rukoh Banda Aceh in solving the problem about the story in terms of cognitive style reflective and impulsive. This study uses a qualitative method. This research was conducted in Banda Aceh MTsN Rukoh in class VII. Sources of data obtained from observation, MFFT, tests and interviews. Examination of the validity of the data is done by triangulation of time. Data analysis was carried out through several stages of data reduction, data presentation and conclusion. Based on the results obtained: (1) the thinking of students who styled cognitive reflective as follows: (a) the students are able to understand the problem; (b) the students have been able to make a plan or a way to solve problems and create a relationship between the known data with data asked in question; (c) the student is capable of running plans have been made, by operating the known data on the matter to the steps that have been made, and then execute the plan. Having obtained the results of the plan and then operate on the issues in question; (d) look back at what has been done or checked back in. (2) the thinking of students whose cognitive style Impulsiveness as follows: (a) the students are able to understand the problem; (b) students make settlement by relying intiusi so that the answer given was one of the students to operate on a mathematical concept; (C) the student is capable of running plans have been made, but in running student plan is still lacking precision in understanding the steps to resolve the matter in question; (d) a student can not make a conclusion on the question of.